Flashman & the angel of the Lord from the Flashman papers, 1858-59 - Fraser, George MacDonald 1925-2008 (Plume, 1996)
Captain Harry Flashman's covert missions for Her Majesty's Secret Service have taken him all over the globe--Afghanistan, Borneo, Madagascar, Indian and China--but never before has he encountered so formidable a challenge and attempted to rise to it with such hilarious ineptitude as in his latest adventure.